SIMRS Implementation Model Using Prism Approach in Medical Record Unit at C Hospital - Sri Rejeki Amelia; Supriyantoro Supriyantoro; Mus Aida (Journal of Multidisciplinary Academic, 2021)
SIMRS is an integrated information system activity, starting from data collection, data processing, data storage, and reporting or presentation of information on health services in hospitals. C Hospital has implemented SIMRS implementation since early 2019. The objective in this study is develop hospital management information systems in supporting the effectiveness of health services at C Hospital. Due to the importance of factors affecting SIMRS in the medical record unit, it is necessary to analyze the information system. In addition, the status of information systems is already running and the effectiveness of health services in hospitals. Thus, this study aimed to obtain empirical evidence of the influence of stakeholder satisfaction factors, processes, strategies, capabilities, and stakeholder contributions to the implementation of SIMRS in the medical record unit and to analyze the factors that inhibit and support the effectiveness of health services. This research method is use mixed method to process the data. Here, the data sources were obtained from primary data and secondary data and collected by distributing questionnaires to 90 respondents and analyzed using multiple linear regression methods. Furthermore, we also use in-depth interviews with six informants to collect the support data. Here, respondents are SIMRS users in the registration unit, outpatient care, emergency room, support, medical records, and IT officers. The results showed that the factors of stakeholder satisfaction, processes, strategies, capabilities, and stakeholder contributions had a significant positive effect on the implementation of SIMRS either partially or simultaneously. The most dominant variable affecting SIMRS implementation is stakeholder satisfaction. Increasing stakeholder satisfaction will further increase the implementation of SIMRS in the medical record unit at RSUD “C”.